Detection and localization of deep endometriosis by means of MRI and correlation with the ENZIAN score. Issue 4 (April 2015) - Di Paola, V.; Manfredi, R.; Castelli, F.; Negrelli, R.; Mehrabi, S.; Pozzi Mucelli, R.
Highlights: The accuracy of MRI for deep endometriosis was 95%. The agreement between histopathological and MRI ENZIAN score was excellent ( k  = 0.824). The highest agreement was for adenomyosis (1.000) and lesions of utero-sacral ligaments (0.890). MRI ENZIAN score allows to obtain a correct preoperative staging of deep endometriosis. Abstract: Purpose: To determine the accuracy of ENZIAN score, as detected on MR imaging, compared to surgical-pathologic findings. Materials and methods: This retrospective study was approved by the investigational review board and the requirement for informed patient consent was waived. 115 patients were included according to following criteria: tubo-ovarian and/or deep endometriosis suspected at physical examination and transvaginal ultrasound; availability of MR examination; histopathological results from laparoscopic or surgical treatment. Exclusion criteria: lack of available MR examination, and/or (b) lack of a definitive histopathological results. Histopathological findings from bioptic specimens obtained during laparoscopic or laparotomic treatment were considered as reference standard. For all detected lesions a score according to ENZIAN score (revised 2010) was assigned both for MRI and histopathological findings. By comparing MRI-ENZIAN score and histopathological-ENZIAN score the overall sensitivity, specificity, accuracy, positive and negative predictive values in relation to presence/absence of deep endometriosis in each patient were calculated. k-Cohen to evaluate the degree of concordance between MRI-ENZIAN score and histopathological-ENZIAN score was also measured. Moreover the sensitivity, specificity, accuracy, positive and negative predictive values for each specific localization provided by ENZIAN score were also calculated. Results: At histopathology, the diagnosis of deep endometriosis was confirmed in 82/115 (71.3%) patients. The sensitivity, specificity, accuracy, PPV and NPV of MRI were 94%, 97%, 95%, 99%, 86%, respectively. The highest accuracy was for adenomyosis (100%) and endometriosis of utero-sacral ligaments (USLs) (98%), slightly lower for vagina-rectovaginal septum an colo-rectal walls (96%), and the lowest for bladder endometriosis (92%). The concordance between histopathological and MRI ENZIAN score was excellent ( k  = 0.824); in particular it was 0.812 for lesions in vagina-rectovaginal space, 0.890 for lesions in USL, 0.822 for lesions in rectum–sigmoid colon, 1.000 for uterine adenomyosis, and 0.367 for lesions located in the bladder wall. Conclusion: MRI correlates with the ENZIAN score and has an accuracy of 95% in the detection and localization of deep endometriosis, allowing to minimize false negative results (4%) in patients with deep endometriosis and to obtain a correct preoperative staging.